Pediatric Extramedullary Epidural Spinal Teratomas: A Case Report and Review of the Literature. (7th October 2021) - Deckey, David G.; Fernandez, Andrea; Lara, Nina J.; Taylor, Steve; McClendon, Jamal; Bennett, David M.
Abstract : Background . Teratomas in the pediatric population are most commonly found in the sacrococcygeal region. Pediatric intraspinal teratomas, however, are an exceedingly rare central nervous system (CNS) neoplasm. The clinical presentation of these intraspinal neoplasms can vary significantly and thus can be difficult to identify in infants less than one year of age where verbal expression and motor development are still lacking. Case Description . A 7-month-old, previously healthy male presented with a thoracic scoliosis and an asymptomatic right midupper thoracic spinal prominence present since birth. MRI revealed an extensive heterogenous mass in the right epidural space from T5-T6 and the right paravertebral space, resulting in severe spinal stenosis. Outcome . Complete resection of the tumor, including a three-level neurotomy, was achieved by posterior decompression/laminectomy. The final tumor was consistent with a mature teratoma. The surgical resection was performed without any immediate complications. Conclusions . Extramedullary epidural teratomas are exceptionally rare tumors in the pediatric population. Clinical presentation can be ambiguous, particularly in an infant. MRI was useful in suggesting a teratoma as a potential diagnosis and for postoperative surveillance for recurrence. However, histopathological analysis remains the gold standard for definitive diagnosis. Surgical resection is the mainstay of treatment, especially in the setting of cord compression and progressive loss of motor function. Close follow-up is crucial to monitor for progressive spinal deformity or recurrence.